The Effect of Argument-Driven Inquiry Using the Science, Environment, Technology, and Society Approach on Students Critical Thinking Skills in Thermochemistry Instruction - Muzainah, Muzainah; Muntholib*, Muntholib; Munzil, Munzil; Affriyenni, Yessi (Universitas Syiah Kuala, 2024)
Thermochemistry is a challenging topic in chemistry learning due to students difficulty in grasping its concepts, often stemming from a lack of critical thinking skills (CTS). This study investigates the impact of using argument-driven inquiry (ADI) learning with a science, environment, technology, and society (SETS) approach on the critical thinking skills of high school students studying thermochemistry. This research, employing a quasi-experimental design with a pretest and posttest control group, involved 46 students divided into a control and experimental group. The control group received ADI learning, while the experimental group received ADI learning with the SETS approach. The instrument used in this research is a CTS test on thermochemitry. It contains five valid questions and has a reliability score of 0.708. The analysis was performed using the Independent t-Test. The CTS test results revealed a significant difference between the groups with the experimental group (15.91) scoring higher than the control group (12.78). This suggest that incorporating the SETS approach into ADI learning can enhace students CTS